REKONSTRUKSI KEBIJAKAN PERLUASAN WILAYAH KOTA BUKITTINGGI: PERSPEKTIF HUKUM DAN IMPLIKASI TERHADAP PEMBANGUNAN DAERAH - Putra, Ridwan; Sari, Hilda Elsa; Maizen, Safii (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Government Regulation Number 84 of 1999 signed by the President of the Republic of Indonesia (B.J. Habiebie) regarding the expansion of the Bukittinggi City area by taking several districts from Agam Regency. This research aims to analyze the reconstruction of the Bukittinggi City expansion policy in the perspective of Government Regulation Number 84 of 1999. The regional expansion policy is one of the local government's efforts to improve the efficiency of public services and regional development. The research method used is a normative juridical approach. Based on the results of research and discussion, it shows that the process of expanding the area of Bukittinggi City faces various challenges, including legal, administrative, and social problems. The implementation of Government Regulation No. 84/1999 has not been optimally applied, due to the lack of coordination between related institutions and minimal public participation. Therefore, an effective policy reconstruction is needed by involving all stakeholders to achieve sustainable development goals. Recommendations from this research are to strengthen the legal and regulatory framework, improve institutional (government) capacity, and expand community participation in the decision-making process related to regional expansion.Keywords: Bukittinggi, Implementation, Policy, Reconstruction, PP 84, West Sumatra,